A reflection on a humanistic approach to narrative inquiry into the lived experience of women casual academics. Issue 4 (3rd July 2016) - Crimmins, Gail
Abstract: Qualitative research is said to add flesh to the bones of quantitative data, and narrative inquiry, more specifically, is described as emotionally comforting, reassuring and validating for participants who share their stories. But little is said of the impact of the flesh, bone and emotions of the narrative inquirer on the qualitative research process. This paper explores a humanistic approach to a narrative inquiry into the lived experience of women casual academics in Australian universities, and exposes the emotional and embodied labour involved in researching others' stories. Through reflecting in and on her practice as a narrative inquirer, the author discusses how she was affectively and ideologically motivated to investigate the lives of women casual academics and demonstrates how her heart worked in conjunction with her head when 'handling' the narrative data. The author finally explores how reflecting on a humanistic approach to narrative research exposes that emotional and cognitive alignment can create research 'flow', and that fully embodied engagement with research aligns with 'slow' and feminist 'in-the-making' scholarship where journey and outcomes emerge and cannot be pre-determined.